2023
DOI: 10.1001/jamahealthforum.2023.0511
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Research Spending on New Drug Approvals by the National Institutes of Health vs the Pharmaceutical Industry, 2010-2019

Abstract: ImportanceGovernment and the pharmaceutical industry make substantive contributions to pharmaceutical innovation. This study compared the investments by the National Institutes of Health (NIH) and industry and estimated the cost basis for assessing the balance of social and private returns.ObjectivesTo compare NIH and industry investments in recent drug approvals.Design, Setting, and ParticipantsThis cross-sectional study of NIH funding associated with drugs approved by the FDA from 2010 to 2019 was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…First, as others have shown, the Bentley University team notes that virtually all new FDA-approved drugs can be traced to some NIH funding. Second, the results reported by Cleary et al indicate large spillover effects of basic research into commercial product development. This finding of spillover effects is consistent with analyses by Li et al, who reported that while 10% of NIH grants result in patents, 30% result in publications cited in patent applications.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…First, as others have shown, the Bentley University team notes that virtually all new FDA-approved drugs can be traced to some NIH funding. Second, the results reported by Cleary et al indicate large spillover effects of basic research into commercial product development. This finding of spillover effects is consistent with analyses by Li et al, who reported that while 10% of NIH grants result in patents, 30% result in publications cited in patent applications.…”
mentioning
confidence: 95%
“…Two articles published in JAMA Health Forum bring some new data and analysis to a debate about the apportionment of credit for new prescription drugs that has been raging since the 1950s . Some have characterized the debate as being a question of whether taxpayers are paying twice for drugs when they pay high prices for prescription drugs and make significant appropriations to the support of the National Institutes of Health (NIH).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In sum, the starting point for an initial offer will be based on the net price of therapeutic alternatives, with a ceiling price based on the lower end of either a percentage of the nonfederal average manufacturer price or the average current net price to Part D plans. This initial offer can be adjusted upward or downward based on several factors, including the research and development costs or the federal support for the drug’s discovery . MEAs have not been a specific discussion point in the recent memorandum, but may evolve in the future as a possible arrangements for price negotiations of drugs.…”
mentioning
confidence: 99%